The composition of posthuman bodies. Issue 2 (3rd July 2017) - Wilson, Samuel
ABSTRACT: A collision of two thoughts on prostheses provides a point of theoretical ignition for this article: the first is that 'the musical instrument is a prosthetic augmentation of the human body, enabling the body to exceed itself' [Johnson, Julian. 2015. Out of Time: Music and the Making of Modernity. Oxford: Oxford University Press]; the second is that 'the posthuman view thinks of the body as the original prosthesis we all learn to manipulate' [Hayles, N. Katherine. 1999. How We Became Posthuman: Virtual Bodies in Cybernetics, Literature, and Informatics. Chicago: University of Chicago Press]. I consider how musical prostheses critically bring into focus the cultural and material conditions of recent modernity. I suggest that by compositionally engineering bodies in posthuman terms, one may dissolve the body into its nonhuman extensions, such that it may be, paradoxically, located therein; through engaging, for example, cyborg identities, bodily extensions enable the body's possession, in transformed terms, during a historical moment when the embodied nature of the subject is in crisis. Brian Ferneyhough's Time and Motion Study cycle (1971–1977), in which the composer entangles performers with technological networks, provides a principal frame of musical and historical reference.